2022
DOI: 10.3390/ijms232113014
|View full text |Cite
|
Sign up to set email alerts
|

Stearoyl CoA Desaturase-1 Silencing in Glioblastoma Cells: Phospholipid Remodeling and Cytotoxicity Enhanced upon Autophagy Inhibition

Abstract: Modulation of lipid metabolism is a well-established cancer hallmark, and SCD1 has been recognized as a key enzyme in promoting cancer cell growth, including in glioblastoma (GBM), the deadliest brain tumor and a paradigm of cancer resistance. The central goal of this work was to identify, by MS, the phospholipidome alterations resulting from the silencing of SCD1 in human GBM cells, in order to implement an innovative therapy to fight GBM cell resistance. With this purpose, RNAi technology was employed, and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…LPCAT1-derived saturated PC (e.g., PC (30:0)) is essential for tumor growth . The saturation of phospholipids also contributes significantly to cell proliferation . Some works reported that controlling the membrane structure and signaling activity by regulating PC saturation determined the invasive behavior of cancer cells. ,, The plasmalogen lipids (e.g., PC O-34:3) regulate many aspects of cell membrane homeostasis, including signal transduction, cell proliferation, and reduction of oxidative stress. , The plasmalogen lipids are potential prognostic biomarkers for CRC metastasis .…”
Section: Resultsmentioning
confidence: 99%
“…LPCAT1-derived saturated PC (e.g., PC (30:0)) is essential for tumor growth . The saturation of phospholipids also contributes significantly to cell proliferation . Some works reported that controlling the membrane structure and signaling activity by regulating PC saturation determined the invasive behavior of cancer cells. ,, The plasmalogen lipids (e.g., PC O-34:3) regulate many aspects of cell membrane homeostasis, including signal transduction, cell proliferation, and reduction of oxidative stress. , The plasmalogen lipids are potential prognostic biomarkers for CRC metastasis .…”
Section: Resultsmentioning
confidence: 99%
“…SCD-1 knockdown was shown to re-sensitize cells to TMZ treatment, while a combined therapy of TMZ and SCD-1 inhibitor was found to reduce the mobility and viability of GBM cells [98]. A study of the phospholipidome proposed that silencing SCD-1 might help to overcome GBM treatment resistance in combined therapies [99]. Moreover, several intracranial tumors including GBM were shown to display high or increased activity of the LDL receptor, a receptor responsible for cholesterol transportation, making these cells highly dependent on cholesterol supply [100].…”
Section: Lipid Uptake and Storagementioning
confidence: 99%
“…Zhang et al showed that SCD1 was essential to stem cell-like behavior and chemoresistance in gastric carcinoma [ 165 ]. Morais et al [ 166 ] and Parik et al [ 167 ] showed that glioblastoma aggressiveness and temozolomide resistance depended on SCD1 expression. Lien et al showed that in vivo PDAC growth under low lipid dietary availability was strongly dependent on SCD1 [ 168 ].…”
Section: Detailed Description Of the Steps In The Lmrs Hypothesismentioning
confidence: 99%